Beyond Stasis: The Medium of Moving Bodies in the Work of Choreographer Ginette Laurin - Cherney, Niomi Anna (eTopia, 2010)
The following paper proposes a model for considering the nature of embodiment through the lensof contemporary dance. The primary aim of this study is to examine the methods through whichthe medium of performance can offer insight into the specificities of the lived body. I pose thematerial body as site of intercorporeal exchange and as a locus of dialogue. Rather thanaccounting for the body as always already being in motion, scholarship on the body has atendency to consider it as a static and concrete form. In order to develop a methodology fortheorizing the lived experience of corporeality, I consider the work of Montreal choreographerGinette Laurin’s evening length work, La Chambre Blanche, by way of example. It is the aim ofthis paper to suggest that a collaborative engagement of Brian Massumi’s post-Deleuzian body,alongside a reading of the traditional phenomenological model of Maurice Merleau-Ponty’snotion of “the flesh” (1968), may provide the tools necessary for a comprehensive reading of thebody in motion.